Avaliação toxicológica de dois antibióticos com o uso do teste Allium cepa - Henrique, Francini dos Reis (2014)
The presence of antibiotics in the environment has been detected, making it necessary to evaluate what consequences they may bring to different levels of the food chain. Many studies have shown the toxic effects of this drugs’ class in different types of aquatic organisms such as algae, fish, Dapnhia spp. and other crustaceans. The Allium cepa test is a test of environmental monitoring already used to toxicological analysis of pesticides, metals and chemicals. The goal of this study was to evaluate the toxic effects that the antibiotics sulfamethoxazole (SMX), trimethoprim (TMP) and it’s mixture (MIX) in similar concentrations to those found in rivers, can cause Allium cepa Allium cepa. Four different concentrations were analyzed in each antibiotic and in the mixture, 3,9 µg.L-1 ,7,8 µg.L-1 , 15,6 µg.L-1 , 31,2 µg.L-1 . A germination test was performed with 10 seeds of Allium cepa to each concentration of each antibiotic and mixture. Tests of chromosome aberrations, cell counts and determination of mitotic index from exposure of roots bulbs to the antibiotics tested were also performed. In germination the SMX showed significantly differences from its control in concentrations 3,9 µg.L-1 and 15,6 µg.L-1 that inhibited the germination, the TMP showed significant results at 15,6 µg.L-1 that stimulated the germination and the mixture showed no significant results. Regarding to the mitotic index (IM), the mixture in concentrations of 3,9 µg.L-1 ,7,8 µg.L-1 and 31,2 µg.L-1 and SMX 7,8 µg.L-1 , had their mitotic index decreased significantly when compared to their respective controls and the TMP showed no significant results. In cell division phases, statistically significant differences were found in telophase of SMX 7,8 µg.L-1 , MIX 3,9 µg.L-1 , 15,6 µg.L-1 and 31,2 µg.L-1 , and in anaphase of SMX 3,9 µg.L-1 . Aberrations such as C-metaphase, metaphase with chromosome loss, binucleated cells in metaphase, metaphase with chromosome adherence and chromosome brigdges in anaphase were found in MIX 3,9 µg.L-1 , 7,8 µg.L-1 , 15,6 µg.L-1 , in all concentrations of SMX and in TMP 7,8 µg.L-1 and 31,2 µg.L-1 . From the results obtained it can be stated that the mixture is cytotoxic to Allium cepa due to the significant decrease of IM when compared to the control; the samples when assessed as the frequency of anaphases of cells division demonstrated a trend towards lower reaction due to the increased number of anaphases, except TMP 31,2 µg.L-1, however only SMX 3,9 µg.L-1 indicated this significantly lower speed, and the present aberrations suggests a genotoxic potencial which needs a more profound quantitative analysis for confirmation.